Analysis on the Perforation of Ductile Metallic Plates by APM2 Bullets. Issue 1 (March 2013) - Chen, Xiaowei; Gao, Yubo; He, Liling
By employing the theoretical model of a rigid sharp-nosed projectile perforating the ductile metallic target plate, the present paper reanalyzes the previously published experimental data of APM2 bullet and its hard steel core perforating aluminum armor plates and high-strength steel plates, respectively. Although the bullet deforms during the perforation, the tests confirmed that the perforation is dominated by the hard steel core whereas the brass jacket, lead cap and end cap have limited influence on the perforation. Therein the perforation model of a rigid sharp-nosed projectile may be conducted to analyze the perforation of APM2 bullet. With increasing the thickness of ductile metallic target plate, the inertia effect of target will arise and obviously affect the terminal ballistics. The inertia effect of target must be considered in the scenario of thick target plate. The experimental analysis further confirms that, the ballistic limit is proportional to the square root of target strength and target thickness.